Efficacy and tolerance of oral versus parenteral cyanocobalamin supplement in normalising cobalamin status in dogs with hypocobalaminaemia and chronic enteropathy – a randomised trial - Dor, Cécile (2021)
Hypocobalaminaemia is a common finding in dogs diagnosed with chronic enteropathies (CE). Currently, veterinary textbooks recommend parenteral or oral supplementation, although is it hypothesised that parenteral supplementation might be more effective as it by-passes impaired intestinal absorption. In dogs, two studies have reported equal efficacy of oral and parenteral cobalamin administration of cobalamin. The objectives of this study were to prospectively evaluate whether oral cobalamin supplementation can restore normocobalaminemia in dogs with CIE and hypocobalaminaemia, as effectively as parenteral supplementation. In addition to determine whether oral supplementation is well-tolerated by owners and dogs and to determine whether oral supplementation is effective even in dogs with protein-losing enteropathy, severe hypocobalaminaemia or severe gastrointestinal signs at inclusion. Thirty-seven client-owned dogs with various signs of CE and hypocobalaminaemia were recruited in three UK referral centres. Dogs were randomly allocated to continuous oral or weekly parenteral cobalamin supplementation for 13 weeks. Serum cobalamin concentration, CIBDAI score and body weight were assessed at inclusion, week 7 and week 13. Methylmalonic acid was evaluated at inclusion and at week 13. Quality-of-life, palatability and tolerance questionnaires were fulfilled by owners at the completion of the study. In total, nineteen dogs completed the study. All dogs became normocobalaminemic with oral cobalamin supplementation. There was no statistical difference in cobalamin concentration at week 13 in dogs treated with oral versus parenteral cobalamin, regardless of presence of PLE, severity of initial hypocobalaminaemia and/or CIBDAI score at inclusion. Both treatments were well tolerated by dogs and owners. There was no statistical difference in treatment tolerance between dogs receiving oral versus parenteral cobalamin supplementation. In conclusion, oral supplementation is as effective and well-tolerated as parenteral cobalamin. Oral cobalamin should be considered in hypocobalaminaemia dogs secondary to CIE, regardless of the severity of the clinical presentation and/or measurable variables.